MANAJEMEN PENGELOLAAN BUMDES MITRA WARGA KESIMAN DALAM PENGEMBANGAN WISATA KULINER LORE OMAH - Farra Zhinta Illa Ammru; Hendra Sukmana (Journal Publicuho, 2025)
This study aims to describe the management of BUMDesa Mitra Warga Kesiman in developing Lore Omah culinary tourism. The study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Data analysis is based on the Miles and Huberman model, which includes data collection, reduction, presentation, and conclusion drawing. The focus of the study is based on the four management functions according to Henry Fayol: planning, organizing, directing, and coordinating.vThe results of the study indicate that the management of BUMDesa has been carried out quite well, although it still faces challenges such as limited funds, suboptimal supporting infrastructure, and the need to improve the quality of human resources. In terms of planning, BUMDesa develops a vision, mission, and short- and long-term tourist visit targets. Organisation is carried out through the formation of an organisational structure with task distribution based on competencies. Direction is carried out through training, guidance, and regular direction to members. Coordination involves cooperation between the village government, community, and investors, which is facilitated through deliberations, development proposals, and regular meetings. Overall, the application of management principles has supported increased village income and community welfare. However, to ensure the sustainability and competitiveness of Lore Omah culinary tourism in the future, this study recommends strengthening management through strategic planning, human resource training, product innovation, and multi-stakeholder collaboration.